Feelings of Wellbeing in Adolescents – A Cross-cultural Study of Finnish and Japanese Students - Tuula Merisuo-Storm; Soili Keskinen; Mariko Matsumoto; Kikuyo Aoki; Misuzu Nagai (Uludag University, 2022)
The purpose of this study was to investigate how students studying in sixth and eighth grade in very different contexts evaluate their own psychological wellbeing. The study was conducted with 697 Finnish and 721 Japanese students. The study aimed to explore if there were differences between the wellbeing of Finnish and Japanese male and female sixth and eighth grade students. The same questionnaire was used as a measure in both countries. According to the results, the Japanese students more often suffered from psychosomatic symptoms, symptoms of impulsiveness, social anxiety, and problems of controlling emotions than Finnish students. The Finnish students more often admitted to problems in their social relationships. The eighth graders revealed more symptoms than the sixth graders and the girls more than the boys. The smallest wellbeing score was obtained by Japanese eighth grade girls.